The Canadian Experiment with Voluntary Incomes Restraint, Degree of Labour Organization and Cyclical Sensitivity of Employement - Walsh, William (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1975)
This paper provides a measure of the industrial distribution of the employment impact of monetary and fiscal policies and suggests that organized labour could have expected to have realized very little differential employment benefits from the Commissions package of proposals— prices and incomes restraint in combination with less monetary and fiscal restraint than would otherwise be possible.